History of agriculture in India - Randhawa, M. S. (New Delhi, 1980)
The history of agriculture is closely interwoven with the process of culture, for it is the development of crop and animal husbandry that enabled human beings to find a certain amount of leisure to create the initial ingredients of a civilization.
Keywords: Agriculture-History